2021
DOI: 10.3343/alm.2021.41.6.549
|View full text |Cite
|
Sign up to set email alerts
|

Application of Single-Domain Antibodies (“Nanobodies”) to Laboratory Diagnosis

Abstract: Antibodies have proven to be central in the development of diagnostic methods over decades, moving from polyclonal antibodies to the milestone development of monoclonal antibodies. Although monoclonal antibodies play a valuable role in diagnosis, their production is technically demanding and can be expensive. The large size of monoclonal antibodies (150 kDa) makes their re-engineering using recombinant methods a challenge. Single-domain antibodies, such as "nanobodies," are a relatively new class of diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 93 publications
0
27
0
1
Order By: Relevance
“…Many characteristics of nanobodies render them suitable components in such tests, providing opportunities to utilize them for the detection of other viral antigens in human or animal samples. A comprehensive review on nanobodies for laboratory diagnostic applications can be found here [77].…”
Section: Nanobodies For Diagnostic Applicationsmentioning
confidence: 99%
“…Many characteristics of nanobodies render them suitable components in such tests, providing opportunities to utilize them for the detection of other viral antigens in human or animal samples. A comprehensive review on nanobodies for laboratory diagnostic applications can be found here [77].…”
Section: Nanobodies For Diagnostic Applicationsmentioning
confidence: 99%
“…Recombinant antibody technology has so far provided genetically encoded high affinity reagents for common immunological assays used in fundamental and applied research (1)(2)(3). Peculiar applications such as tracing or modulating intracellular proteins in living cells are ascribed to special antibody fragments or alternative scaffolds that rely on single chain binding domains (4).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Their much smaller size compared to intact IgG antibodies ( � 150 kDa) combined with simple expression, high stability, high solubility, and many chemical functionalization strategies provide NBs with several advantages for biosensing and bioimaging. [6,9,10] To…”
mentioning
confidence: 99%
“…[29] QD FRET acceptor conjugates were prepared depending on the different tags on NB2: i) NB2-H-QD625-CL4: QD625-CL4 were mixed in a 1 : 20 molar ratio with NB2-H, which resulted in efficient metal-affinity mediated self-assembly to the Zn-rich QD surface after � 30 min. [39] Considering the 2.5 nm diameter of NBs, [9] 20 NB2 should take approximately 50 nm 2 of space on the � 265 nm 2 surface of the QD (A = 4πr 2 with r = 4.6 nm), which can be considered as low enough to avoid steric hindrance and allow for efficient self-assembly. ii) NB2-B-QD705-sAv: NB2-B was attached to QD705-sAv via the strong biotin-sAv interaction, [40] also by simple mixing for � 30 min in a 20 : 1 molar ratio.…”
mentioning
confidence: 99%
See 1 more Smart Citation